The Wiley Blackwell Encyclopedia of Urban and Regional Studies 2019
DOI: 10.1002/9781118568446.eurs0321
|View full text |Cite
|
Sign up to set email alerts
|

State‐Led Gentrification

Abstract: State‐led gentrification is a form of gentrification planned, commanded, or promoted by state agencies at national, regional, metropolitan or municipal level, as part of either a nationwide or local‐level restructuring agenda, aimed at generating specific urban and land conditions for gentrification to occur. It is the result of one of several policies designed to promote the opening of economic opportunities for upper income housing production, or even the prescription or direct application of social displace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…The second concerns people, reflecting the replacement of the original users of the space by others of higher socio-economic status. Regarding the push-out effect of gentrification, analyses have tended to explain it in terms of the social class variable, often subsuming others such as race or ethnicity (Fallon, 2020;López-Morales, 2019). However, accumulating evidence has increasingly shown that both migrant populations and racial and ethnic minorities suffer higher levels of exposure to gentrification (Betancur, 2011;Bolt et al, 2009;Goetz, 2011;Hyra, 2018).…”
Section: Immigrants In the Face Of Gentrificationmentioning
confidence: 99%
“…The second concerns people, reflecting the replacement of the original users of the space by others of higher socio-economic status. Regarding the push-out effect of gentrification, analyses have tended to explain it in terms of the social class variable, often subsuming others such as race or ethnicity (Fallon, 2020;López-Morales, 2019). However, accumulating evidence has increasingly shown that both migrant populations and racial and ethnic minorities suffer higher levels of exposure to gentrification (Betancur, 2011;Bolt et al, 2009;Goetz, 2011;Hyra, 2018).…”
Section: Immigrants In the Face Of Gentrificationmentioning
confidence: 99%
“…Estas mismas zonas pueden ser espacios urbanos en los que el Estado, en asociación con firmas extranjeras, reinvierte en la ciudad para atraer flujos financieros, señas de una metropolización que se ha iniciado en esta aglomeración importante del Caribe y cuya fragmentación del espacio por el mercado comienzan a verse más claramente en el paisaje urbano. Como ejemplos se pueden mencionar el Centro de Negocios Miramar construido a partir del 1999 y los grandes hoteles de cuatro o cinco estrellas (Figura 5) que han florecido en los últimos años que favorecen el desembarco de flujos de capital extranjero en áreas que luego se convierten en zonas de inversión y permiten considerar el papel del Estado en la capitalización del espacio urbano (Hackworth y Smith 2001, López-Morales 2019.…”
Section: Turistificación De La Habana Y Mercantilización De La Vivien...unclassified